Pengaruh Lendir Bekicot (Achatina fulica) terhadap Jumlah Sel Fibroblas pada Penyembuhan Luka Sayat Studi Eksperimental pada Kulit Mencit (Mus musculus) - Purnasari, Perez Wahyu; Fatmawati, Dina; Yusuf, Iwang (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2012)
Background: Wound healing is very important to return skin as soon as possible and the integration is a complex and dynamic process. Proliferation phase involving fibroblasts is one of important step-on wound healing. Use of drugs such as povidone iodine on cuts aims to accelerate wound healing is still being debated. Healing by land snails’ mucus can be an alternative because it has many benefits. This study wants to know about the influence of land snails’ mucus on the number of fibroblasts in healing cuts.Design and methods: The study is an experimental research with post test only randomized control group design. The subjects were 18 Mus musculus strain mice that were divided into 3 groups. 1st group as a control group of untreated, 2nd group was given povidone iodine 10%, and 3rd group was given land snails’ mucus during 5th days. On the 6th day the mices were killed for histological study.Results: The data showed that average number of fibroblast in 1st group is 93,85; 2nd group is 126,37; and 3rd is group 217,5. The results of one way anova statistical test showed significant difference among the three groups p = 0,000. The results of post hoc test showed significant difference in all groups (p < 0,05).Conclusion: The mucus of land snail is influence the number of fibroblast in healing cuts (Sains Medika, 4(2):195-203).